รูปแบบการพัฒนาคุณลักษณะผู้นำที่มีความเชื่อมั่นในตนเองของนักเรียนนายสิบทหารบกเหล่าทหารราบ: โมเดลโค้งพัฒนาการที่มีตัวแปรแฝงสมการกำลัง 2 ลำดับที่ 2 (A DEVELOPMENT MODEL OF LEADER’ SELF-CONFIDENCE TRAITS OF NON-COMMISSIONED STUDENTS INFANTRY CROP: 2ND ORDER Q - นิติวิทยากุล, เสน่ห์ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2018)
This research was aimed to develop model of leaders’ self-confidence traits of non-commissioned student infantry crop. The research methodology is a mixed method. The research design was divided into 4 phases: the 1st phase (R: 1) to study the theory of leaders’ self-confidence trait and to develop model (Best practices). the 2nd phase (D:1) was the development model of development leaders’ self-confidence traits (Feasibility) for Prototype solution by using qualitative research and the research tools were interviewing, Observation and focus group. The 3rd phase (R: 2) was an experiment of using model (try out) to compare the growth rate between the control group and experimental group, and the 4th phase (D: 2) was a model improvement and implementation (final solution) by using quantitative research and the research tools by using model of development self-confidence leaders’ traits (Prototype) and questionnaire. The populations were 1,097 students of army non-commissioned, infantry corps, Infantry School. The samples were 70 students derived from the sampling method by G*Power statistical computer program and divided into 2 groups as control group for 35 samples and experimental group for 35 samples. The quantitative data was statistically analyzed by frequency, percentage, means, standard deviations, variances and Cronbach’s alpha using SPSS for Window and 2nd order quadratics LGM statistically analyzed by Chi-square: (c2), Relative Chi-square: c2/df), Degree of freedom (df), RMSEA, CFI, TLI, SRMR, Wald test(DS), intercept means (mi), slope means (ms), quadratics means (mq), intercept variances (s2i), slope variances (s2s), quadratics variances (s2q), slope-intercept co-variances (fs-i), quadratics-intercept co-variances (fq-i) and quadratics-slope co-variances (fq-s) using by Mplus computer program and the qualitative data was the content analysis. The results found that (1) model of leaders’ self-confidence traits were 6 components to develop; Self-Efficacy, assertiveness, decisiveness, self-esteem, optimism, and adaptability for working environment by group process and relationship group activities, (2) In first period the experiment of using model of leaders’ self-confidence traits found that the growth rate of self-confidence leaders’ traits of experiment group was higher increased than the control group in all 6 components at the significant level of .05 but the growth rate decrease in the end (3) the evaluation of model development of self-confidence leaders’ traits by 2nd order quadratics LGM was harmonized with the empirical data. And (4) the research can be concluded that the development model can be able to solve the problem of lacking of student’ self confidence effectively in short time.